Rehabilitation of Depressive Disorders in Persons Having Covid-19 (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
This article examines the indicators of anxiety and depression in patients with COVID-19, which is one of the medical and social problems. The degree of anxiety and depression was assessed using modern neuropsychological scales. Based on the results obtained, an early rehabilitation algorithm was developed.